Selection of the optimal technology to prevent sand production, taking into account rock deconsolidation in the bottomhole formation zone (Rudarsko-geološko-naftni zbornik, 2024)
This article presents studies on the selection of the best sand control option, technologically based on the application of the method of fixing the bottomhole part of the well system with polymerized proppant, which will prevent the destruction of the formation zone of the wells and facilitate the development of the Kumkol field in the future. During the development of the Kumkol field, the main and most complicating factor in the operation of wells is sand production, leading to long downtime and repairs. The aim of the study is to scientifically substantiate and improve the technological methods of fixing the bottomhole zone of the well system to exclude or limit sand production with the well production of the Kumkol field, taking into account the current state of the reservoir rocks. The work applied a set of research methods, including: analysis of the experience of combating sand ingress at the Kumkol field; the use of the theoretical foundations of the relationship between the methods of anti-sand filtration and the properties of reservoir rocks; mathematical experiments on the constructed geological and mathematical model of the current state of the rocks of the decompacted zone. The scientific novelty of the work lies in the establishment of patterns that relate the impact of the destruction of reservoir rocks with a weakly cemented property in a production well on the degree of formation of deconsolidation zones at the bottom of wells that reveal a weakly cemented rock formation.